Potential of fruit waste in promoting in vitro probiotic growth. - Abdul Rahim, Erra Fazira (2021)
Fruit waste (FW) refers to the loss and waste of unneeded or unconsumed components of fruit that are biodegradable. This includes the fruit peel, pulp, seeds, and leaves. FW was reported as a non-conventional alternative source of nutritional and mineral content that might be employed as functional food components. However, the prebiotic significance of FW is poorly recognized. This limitation is overcome by the invention of FW as a prebiotic source through in vitro fermentation on Lactobacillus casei Shirota (L. casei S.) growth. Therefore, the objectives of this study were to investigate the nutritional and mineral composition of FW from banana, orange, and watermelon peels, determine the growth and survival of probiotics using FW as a substrate, and assess the prebiotic potential and metabolites produced from FW through in vitro monoculture fermentation. In this study, the peel cuts were boiled in hot water (90°C) for 30 minutes to inactivate any potential microorganisms and enzyme reactions. The peels were then processed separately into two groups: freeze-dried (FD) and oven-dried (OD). The nutritional properties, mineral composition, and prebiotic activities of FW were analyzed. Both drying techniques were shown to be quite effective in preserving and reducing the FW moisture. Furthermore, the carbohydrate content ranged from 47.74–83.04% dry weight basis, with crude fibre content supplied in greater quantities. There was a wide variety of mineral content detected, with calcium and sodium being the most abundantly generated compounds. It was found that L. casei S. growth in modified de Man Rogosa Sharpe (mMRS) broth enrinched with FW from banana indicated a higher bacterial count and survival rate in comparison with inulin, which ranged from 91.61–98.66%. Thus, it presents an excellent potential substrate for probiotics. Further on, as a prebiotic ingredient, the growth density of L. casei S. through in vitro monoculture fermentation showed a positive prebiotic effect in FW which is higher than inulin, which acts as a positive control. Samples obtained at 0, 6, 12, and 24 hours were evaluated for organic acid production by high-performance liquid chromatography (HPLC), resulting in positive short chain fatty acid (SCFA) production, with butyrate being the major organic acid generated. The study discovered that FW has the potential to enhance probiotic development, act as a source of fermentable substrate, and produce beneficial organic compounds. Thus, it will be able to function as an alternative prebiotic ingredient, which could be a significant contributor to novel functional food applications on a commercial scale.